A Framework for Integrated Postnatal Care Services for Traditional Malay Medicine and Modern Medicine - Raja Ikram, Raja Rina; Mohd Khanapi, Abd Ghani (Research India Publications, 2015)

(untitled)
This paper shall propose aframework to integrate the services of Traditional Malay Medicine (TMM) with modern medicine in the field of postnatal care. A semi structured interview was conducted towards twelve postnatal care practitioners in the traditional malay medicine and modern medicine field and one public hospital in Malaysia. The current framework shows that both medicine systems are being treated in isolation of each other. MyPostnatal framework is proposed to integrate the services of these medicine systems via electronic health records.Patient can access integrated healthcare services seamlessly and holistically without isolation. Healthcare providers shall also benefit from the standardization of information exchange with other healthcare providers.